ANALISIS FAKTOR PERILAKU INDISIPLINER SISWI BERJILBAB DI KELAS X SMA NEGERI 1 SUNGAI AMBAWANG - Fahruji, Fahruji; Fatmawati, Fatmawati; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Title of this research is ?An Analysis To The Students? Behaviour Who Wear Hijab At Tenth Grade Students of SMAN 1 Sungai Ambawang?. The problem of this research was how social regulation to the students who wear hijab at tenth grade students toward  the specific problems such as how was the social value, social norm, and social intercourse system or interaction at the tenth grade students of SMAN 1 Sungai Ambawang In conducting this research, the recearcher use the descriptive method in qualitative form. The tools of data collection were observation guidance, interview guidance and documentation of the study. The result showed that (1) The social valves at SMAN 1 Sungai Ambawang got low attention from the studemts, it was shown by the violation which done by the student, even when already knew about the vegulation.(2) Legal norm existed at SMAN 1 Sungai Ambawang was categorized good, but there were still some students who did not notice it. (3) The social intercourse systeor interaction at SMAN 1 Sungai Ambawang influenced the mostly students behavior.It was shown by the students who break the school regulations were got influence from their friends. Keyword: Behaviour, Social Velve, Social Norm, Interaction.